Electromechanical cell lysis using a portable audio device: enabling challenging sample preparation at the point-of-care1. Issue 9 (7th May 2015) - Buser, J. R.; Wollen, A.; Heiniger, E. K.; Byrnes, S. A.; Kauffman, P. C.; Ladd, P. D.; Yager, P.
<x xml:space="preserve">Abstract</x> Portable lysis of Mycobacterium marinum and Staphylococcus epidermidis bacteria using an mp3 player, electromagnetic coil, and magnet in a tube.